Odonata Of Rice Fields In Poonch And Bagh Districts of Azad Kashmir: ?Short Communications (Biological Sciences - PJSIR, 1995)
Rice (Oryza stiva L.), an important cereal crop of AzadJammu and Kashmir, is grown in an area of 7,000 hectares.However, the average yield is very low (1483 Kglha) andinfestation by a number of insect pests is one of the factorsresponsible for it.